Penerapan Pola Pengasuhan Permisif terhadap Perilaku Agresivitas Siswa di SD Negeri 1 Kapongan - Rizki Maulana Hidayatullah; Finanin Nur Indana; Nur Jamila (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Permissive parenting has a bad influence on a child's character or behavior. The impact of permissive parenting on children includes behavior that contains elements of aggressiveness in the form of verbal or non-verbal. Factors that cause aggressive behavior include bad parenting patterns given by parents. The goal to be achieved in this research is the influence of permissive parenting on aggressive behavior. The sample in the research was 125 students from SD Negeri 1 Kapongan, Situbondo Regency. Data was collected through a scale of permissive parenting patterns modified from (Arifin, 2019) and aggressive behavior modified from (Helmi, 2018). Next, analysis was carried out using statistical regression analysis. Based on the research results, a significant value = 0.000 < 0.05 was produced with the regression coefficient value being positive, therefore the conclusion was drawn that there was a positive influence between permissive parenting patterns on aggressive behavior at SD Negeri 1 Kapongan, Situbondo Regency or it could be interpreted as high levels of permissiveness applied by people. When older, a child's aggressive behavior increases. Likewise, the opposite is true if parents are not permissive in implementing their parenting style, making their children less aggressive in their behavior.